Efficient, Cyanine Dye Based Bilayer Solar Cells. Issue 4 (20th November 2012) - Malinkiewicz, Olga; Grancha, Thais; Molina‐Ontoria, Agustin; Soriano, Alejandra; Brine, Hicham; Bolink, Henk J.
Abstract Simple bilayer solar cells, using commercially available cationic cyanine dyes as donors and evaporated C60 layer as an acceptor are prepared. Cyanine dyes with absorption maxima of 578, 615 and 697 nm having either perchlorate or hexafluorophosphate counter‐ions are evaluated. The perchlorate dye leads to cells with S‐shape current‐voltage curves; only the dyes with the hexafluorophosphate counter‐ions lead to efficient solar cells. When the wide bandgap dyes are employed, S‐shape current‐voltage curves are obtained when the conductive polymer PEDOT:PSS is used as hole transport layer. Substitution of PEDOT:PSS with MoO3 leads to cells with more rectangular current–voltage curves and high fill factors. Additionally, the cells using the MoO3 layer for hole extraction lead to high open circuit voltages of 0.9 V. In the case that a low bandgap hexafluorophosphate dye is used with the HOMO above that of the PEDOT:PSS the cell performance is independent on the type of hole transport layer employed. Using this approach, bilayer solar cells are obtained with power efficiencies ranging from 1.8 to 2.9% depending on the particular dye employed. These are impressive numbers for bilayer solar cell that are partially solution processed in ambient conditions.